Extracellular vesicles derived from the choroid plexus trigger the differentiation of neural stem cells. Issue 11 (2nd November 2022) - Ditte, Zuzana; Silbern, Ivan; Ditte, Peter; Urlaub, Henning; Eichele, Gregor
Abstract: The choroid plexus secrets cerebrospinal fluid (CSF) composed of electrolytes, cytokines, growth factors, metabolites and extracellular vesicles (EVs) that flow through the interconnected brain ventricles. On their course, CSF components can act as signals that affect, for example, neural stem cells (NSCs) residing in niches of the ventricular wall. We studied EV‐born CSF signals in an in vitro culture system. We purified EVs from the secretome of a choroid plexus cell line (Z310 cells), and from primary choroid plexus cultures and co‐cultured those EVs with NSCs isolated from the niche of the lateral and the third ventricle. EVs Z310 and EVs CHP were purified by differential centrifugation. This yielded fractions of EVs of 50–150‐nm diameter that induced a complex multicellular network formation and NSC differentiation. Both types of EV converted the round NSCs to cells that extended long processes that contacted nearby, alike‐shaped cells. Mass spectrometry showed that the differentiation‐inducing EV Z310 were enriched for membrane and membrane‐associated proteins involved in cell differentiation, membrane trafficking, and membrane organization. We hypothesize that this type of EV Z310 cargo causes changes of stem cell morphology that leads to multicellular networks in the niches. This cell‐shape transition may represent an initial step in NSC differentiation.